Employee Responses to Compensation Changes: Evidence from a Sales Firm - Sandvik, Jason; Saouma, Richard; Seegert, Nathan; Stanton, Christopher (Management Science, 2021)
What are the long-term consequences of compensation changes? Using data from an inbound sales call center, we study employee responses to a compensation change that ultimately reduced take-home pay by 7% for the average affected worker. The change caused a significant increase in the turnover rate of the firm’s most productive employees, but the response was relatively muted for less productive workers. On-the-job performance changes were minimal among workers who remained at the firm. We quantify the cost of losing highly productive employees and find that their heightened sensitivity to changes in compensation limits managers’ ability to adjust incentives. Our results speak to a driver of compensation rigidity and the difficulty managers face when setting compensation. This paper was accepted by Lamar Pierce, organizations.